Dynamic of Phenolic Compounds, Antioxidant Activity, and Yield of Rhubarb under Chemical, Organic and Biological Fertilization - Alexandru Cojocaru; Laurian Vlase; Neculai Munteanu; Teodor Stan; Gabriel Ciprian Teliban; Marian Burducea; Vasile Stoleru (Plants, 2020)
In recent years, rhubarb is being increasingly cultivated, as it provides early yields when the vegetables supply to market is deficient and shows high levels of both polyphenols content and antioxidant capacity in edible parts. In 2017, we investigated crops of the rhubarb cultivar Victoria to the fifth year of production. Comparisons were performed between three root phase fertilizations—chemical (NPK 16-16-16®), organic (Orgevit®), and biological (Micoseeds MB®)—plus an unfertilized control. The determinations of polyphenols, the antioxidant capacity, and the yield indicators from the stalks (petioles) of rhubarb were made at each out of the 10 harvests carried out. The highest yield (59.16 t·ha−1) was recorded under the chemical fertilization. The total polyphenols content and antioxidant capacity varied widely from 533.86 mg GAE·g−1 d.w. and 136.86 mmol Trolox·g−1 d.w., respectively in the unfertilized control at the last harvest, up to 3966.56 mg GAE·g−1 d.w. and 1953.97 mmol Trolox·g−1 d.w. respectively under the organic fertilization at the four harvest. From the results of our investigation, it can be inferred that the chemical fertilization was the most effective in terms of yield, whereas the sustainable nutritional management based on organic fertilizer supply led to higher antioxidant compounds and activity.